Environmental education as a key factor of environmental consciousness - ISAKOVA, Nataliia; DANKEVYCH, Liudmyla (Journal of Education, Technology and Computer Science, ISSN 2719-6550, e-ISSN 2719-7417, 2013)
Understanding the phenomenon of environmental education and implementationof its principles in the cultural life of our contemporary is an urgent problemof today. The integrity of the natural environment for human existence, andthe acquisition of skills necessary for an individual in the contemporary societydepend on the level of environmental upbringing and environmental educationof people, and the younger generation, in particular. Environmental educationaims to help people understand the causes of environmental changes and to proposethe ways to prevent them.The article highlights the aims, subject matter & peculiarities of environmentaleducation, its influence on the formation of environmental consciousnessof the younger generation in Ukraine. Environmental knowledge is regarded asa prerequisite for the development of environmental consciousness, and theirsuccessful acquisition forms environmental outlook.